The unmet supportive care needs of Chinese patients and caregivers affected by cancer: A systematic review - Wu, Verena Shuwen; Smith, Allan Ben; Girgis, Afaf (European journal of cancer care, 2022)
Introduction Cancer patients and caregivers have myriad unmet needs which can have detrimental consequences on their psychosocial wellbeing. This systematic review aims to identify the unmet supportive care needs of immigrant and native Chinese cancer patients and caregivers. Methods We systematically searched various electronic databases (e.g. Scopus, CINAHL, PsycInfo, etc.) from the earliest date available until January 2018. Additional studies were identified through reference lists and citation tracking. Eligibility criteria included: (a) qualitative, quantitative and/or mixed methods studies published in English; (b) immigrant and native Chinese cancer patients and/or caregivers (age ≥18 years); (c) unmet needs and/or their correlates. Studies were assessed for their risk of bias, and a narrative synthesis of findings was performed. Results Forty‐seven papers from 45 studies met eligibility criteria. The most prevalent area of unmet needs was health system and information. Patients most commonly desired one member of the hospital to talk to about all aspects of their care. Caregivers preferred information about the patient's prognosis and likely outcome. Anxiety was most commonly associated with higher levels of health system and information needs. Conclusion Chinese patients and caregivers experience a range of unmet health system and information needs, which differ depending on their stage along the cancer trajectory.